ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2011) - Fira Fimanaya; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2014)
This research was conducted to examine the effect of pressure, opportunity and rationalization to the possibility of fraudulent financial statement . This research used secondary data. Population in this research is the all non-financial companies listed on the Indonesia Stock Exchange in 2008 and 2011. Sampling method used is purposive sampling. The criteria that companies committing fraud is BAPEPAM regulation offenses no. VIII.G. . on guidelines for the presentation of financial statements. The analysis technique used in this research is logistic regression with stepwise method. The results of the analysis showed that the profitability variables had negatively affect to the possibility fraudulent financial statements. While financial leverage variables, the ratio of capital turnove , related party transactions, audit firm size, the ratio of inventory per total asset, change of auditors, the audit opinion, and the ability of Going Concern had no significant effect.